Rare male mating advantage in a natural population of Drosophila pseudoobscura. - Salceda, V M (1988)
The natural selection acting on chromosomal inversions was studied in a natural population of Drosophila pseudoobscura. Females from this population were allowed to produce offspring from their matings in nature. They were then remated to males from a laboratory strain and again allowed to produce offspring. Offspring were also produced from matings of males from nature to laboratory females. Diagnosis of salivary chromosomes in these several sets of larval offspring allowed us to deduce the karyotypes of adult females and males from nature as well as the karyotypes of the offspring of these females by their matings in nature. We reason that the males collected with the females are a reasonable sample of those that mated the females and deposited the sperm they carried on capture. Chromosome frequencies in the offspring of wild females by their matings in nature were decomposed into male and female parental contributions. Changes in chromosome frequency due to male mating success were calculated by comparing chromosomal frequencies in adult males with those in the chromosomes they contributed to their offspring. These changes were sizable and provide direct evidence that male sexual selection is an important component of selection on the inversions in this natural population. We proceeded further to classify karyotypes on the basis of their frequencies and to calculate the fraction of offspring fathered by rare or common males. Rare male karyotypes as a group had a selective value nearly twice that of the common male karyotypes.